COMMITTEE OF ELIMINATION RACIAL DISCRIMINATION (CERD) ACTIONS AGAINST ISRAEL'S ETHNIC CLEANSING CRIMES AGAINST PALESTINE - Mahli, fahrurrozi; Shufiyah Qulub, Andi; Affazul Muna, Inas (fakultas hukum universitas PGRI Semarang, 2024)
Palestine’s importance in debates about race, and racism in international law stems largely from the Zionist movement’s attempt to establish a new settler colonial state in an era when decolonization and liberal rejection of racism were rife around the world. The Nakba 0f 1948 will be repeated on October 7, 2023. this article wants to see the actions and responses of the Committee of Elimination of Racial Discrimination (CERD) to ethnic cleansing carried out by Israel againts Palestinians and the response of third countries to Israel’s action againts Palestinians. The method used is the normative research method. The result of this research are CERD which has carried out several working mechanisms, such as warnings, inter-State communication, the establishment of an Ad Hoc Conciliation Commission, and calls by experts in the form of insistence in the Session. Countries that responded to this conflict such as Indonesia, Jordan, and Iran, took action to boycott products affiliated with Israel and encouraged Islamic countries to sanction Israel